Prognosis of low-flow low-gradient aortic valve stenosis with atrial fibrillation. (3rd October 2022) - Nishinarita, R; Arao, K; Sugisaki, K; Yamashita, T; Yozawa, A; Kasahara, T; Mase, T
Abstract: Background: Patients with Low-flow low-gradient (LFLG) aortic valve stenosis (AS) have possibly poor prognosis. Recently, it was reported that the LFLG AS patients have similar outcomes compared to high-gradient (HG) patients but worse outcomes compared to the normal-flow low-gradient [NFLG: SVi≥35 ml/m 2, mPG <40mmHg] subgroup. The main determinant of LF state in severe AS patients with preserved LVEF are male gender, heart rate, LV volume and atrial fibrillation (AF). However, the relationship between the comorbidity with AF in LFLG AS and the risk of heart failure (HF) remains unclear. Purpose: We elucidated about the prognosis of LFLG AS with AF. Methods: We included 225 consecutive patients with severe AS (SAS, iAVA<0.6 cm 2 /m 2 ) from 2013 to 2020. Among these patients, high-gradient SAS [HG-SAS; mean pressure gradient (mPG) ≥40 mmHg, n=88] and LFLG AS [stroke volume index (SVi) ≤35 ml/m 2, mPG <40 mmHg, n=82] patients was extracted and the baseline characteristics including the presence or absence of AF were evaluated. The primary endpoint was worsening HF that required unplanned hospitalization or readjustment of HF drug therapy. Results: Among patients with HG SAS and LFLG AS, worsening HF was observed in 65 patients. LFLG AS patients exhibited a higher oral rate of renin-angiotensin-system inhibitors (p=0.02). In addition, SVi and E/e' was lower in LFLG AS patients compared with HG SAS [SVi; 29.4 (24.4–34.0) versus 37.7 (28.2–45.3), p<0.0001, E/E'; 16.0 (13.1–21.5) vs 20.9 (16.0–27.4), p=0.002]. There is no differences between 2 groups in AF prevalence. Furthermore, 2 groups were subdivided as follow; HG SAS with AF (n=25), HG SAS without AF (n=63), LFLG AS with AF (n=24), LFLG AS without AF (n=58). The Kaplan Meier curves demonstrated LFLG SAS with AF experienced higher rate of worsening HF compared with HG SAS without AF and equivalent rate of worsening HF compared with HG SAS with AF (log rank, p<0.001). In the Cox hazard analysis among the LFLG AS patients, LFLG AS with paroxysmal AF (pAF, n=12) instead of chronic AF (cAF, n=12) showed a higher risk for worsening HF compared with those without AF (HR 5.0; 95% CI, 1.8–14; p=0.0028, HR 1.9; 95% CI, 0.62–5.8; p=0.26, respectively). Conclusion: LFLG AS with AF exhibited a poor prognosis for HF compared with HG SAS without AF and equivalent rate of worsening HF compared with HG SAS with AF. Furthermore, the presence of pAf was associated with an increased risk of HF in patients with LFLF AS. Thus, intervention including drugs and catheter ablation for pAF in LFLG AS patients could lead to prevent worsening clinical outcomes. Funding Acknowledgement: Type of funding sources: None.